Asymmetrical Interhemispheric Connections Develop in Cat Visual Cortex after Early Unilateral Convergent Strabismus: Anatomy, Physiology, and Mechanisms - Bui Quoc, Emmanuel; Ribot, Jérôme; Quenech'Du, Nicole; Doutremer, Suzette; Lebas, Nicolas; Grantyn, Alexej; Aushana, Yonane; Milleret, Chantal (Frontiers in Neuroanatomy, 2012)
In the mammalian primary visual cortex, the corpus callosum contributes to the unification of the visual hemifields that project to the two hemispheres. Its development depends on visual experience. When the latter is abnormal, callosal connections must undergo dramatic anatomical and physiological changes. However, such data are sparse and incomplete. Thus, little is known about the consequences of abnormal postnatal visual experience on the development of callosal connections and their role in unifying representation of the two hemifields. Here, the effects of early unilateral convergent strabismus (a model of abnormal visual experience) were fully characterized with respect to the development of the callosal connections in cat visual cortex, an experimental model for humans. Electrophysiological responses and 3D reconstruction of single callosal axons show that abnormally asymmetrical callosal connections develop after unilateral convergent strabismus, resulting from an extension of axonal branches of specific orders in the hemisphere ipsilateral to the deviated eye and a decreased number of nodes and terminals in the other (ipsilateral to the non deviated eye). Furthermore this asymmetrical organization prevents the establishment of a unifying representation of the two visual hemifields. As a general rule, we suggest that crossed and uncrossed retino-geniculo-cortical pathways contribute in succession to the development of the callosal maps in visual cortex.